Perancangan Dan Pembuatan Evaporator Pada Sistem Organik Rankine Cycle (ORC) Menggunakan Fluida Kerja R-134A Untuk Pembangkit Listrik Kapasitas 1 KW - Okvitasari, Dwi Yani; Martin, Awaludin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Waste heat from industries such as steam power plants can be utilized to meet the world’s electricity need. However, it cannot be converted efficiently to electric power by using conventional power generation methods, a technology for converting it is called Organic Rankine Cycle (ORC). ORC is one of the power plant systems that is a modification of Rankine Cycle using organic working fluid. R-134a was used as working fluid. The selection of working fluid was assisted by using Cycle Tempo and REFPROP software which has function to simulation of power plant and determine the thermodynamic properties, respectively. ORC system consisting of four key components: evaporator, turbine, condenser, and pump. In this study, we designed a shell and tube type evaporator, where it is designed from a large cylindrical tube called a shell assembled with a parallel pipe. Flow arrangement of evaporator is parallel-flow. Design of evaporator was 400mm shell length, 360mm shell diameter, 9.525mm OD tube, 8.407mm ID tube, tube length 10.57m, 250mm helical tube diameter, 300mm helical tube height and 13.5 the revolution of tube.Keywords: Organic Rankine Cycle, Design, Manufacturing, R-134a